2022
DOI: 10.3390/ijms23052427
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Therapy Attenuates Phospholamban p.(Arg14del) Cardiomyopathy in Mice and Reverses Protein Aggregation

Abstract: Inherited cardiomyopathy caused by the p.(Arg14del) pathogenic variant of the phospholamban (PLN) gene is characterized by intracardiomyocyte PLN aggregation and can lead to severe dilated cardiomyopathy. We recently reported that pre-emptive depletion of PLN attenuated heart failure (HF) in several cardiomyopathy models. Here, we investigated if administration of a Pln-targeting antisense oligonucleotide (ASO) could halt or reverse disease progression in mice with advanced PLN-R14del cardiomyopathy. To this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Along those lines, treatment with the small molecule istaroxime that stimulates SERCA2a activity had beneficial effects in the PLN-R14del zebrafish model as it An alternative gene targeting approach includes the use of antisense oligonucleotides (ASO), which bind to a specific mRNA target resulting in mRNA degradation and enable elimination of a mutant protein without the need for genetic modifications (84). The applicability of this approach in the setting of PLN-R14del pathology was recently investigated in the mouse PLN-R14del knock-in model (82,83). Administration of a Pln-targeting ASO in homozygous PLN-R14del mice prevented PLN aggregation, cardiac remodeling and cardiac dysfunction, leading to a 3-fold increase in survival rate (83).…”
Section: Precision Medicine Strategies Towards Targeted Pln-r14del Th...mentioning
confidence: 99%
“…While it is still unknown what triggers PLN aggregate formation, structural alterations of PLN-R14del may cause protein misfolding that could promote its aggregation. The presence of autophagy marker proteins such as p62 and LC3 within PLN aggregates, along with alterations in their expression levels, indicates inefficient protein degradation by the autophagy pathway and depressed proteostasis ( 48 , 82 ). This defect, along with Ca 2+ mishandling, may be directly or indirectly implicated in activation of compensatory mechanisms such as UPR in order to alleviate ER stress and maintain proteostasis.…”
Section: Existing Knowledge Of Pln-r14del Pathogenetic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation